Executive ethical decisions initiating organizational culture and values. Issue 5 (10th September 2018) - Bridges, Eileen
Abstract : Purpose: Ethical decisions determine which individuals and/or groups benefit, and which suffer. Such decisions by executives impact front-line providers directly and customers indirectly; they are important because repercussions in service interactions feel personal. The purpose of this paper is to fill an important gap in the service literature by exploring how high-level executives make ethical decisions, creating values and culture within an organization; the results include testable propositions. Design/methodology/approach: The research used a grounded theory approach, wherein high-level executives in successful service organizations responded through in-depth interviews. Complete interview transcripts were analyzed using standard qualitative methodology, including open coding to better understand and categorize the data, axial coding to seek out crucial relationships between concepts, and selective coding to develop research propositions. Findings: Data analysis revealed two groups of interviewees, one more outcome-oriented in decision making and the other more process-oriented. The organizations led by more outcome-oriented executives have strong family-like (or paternalistic) cultures, whereas the organizations led by more process-oriented executives value adaptability and diversity. Research limitations/implications: The executives interviewed are quite successful; therefore, it is not possible to make inferences about unsuccessful executives or those leading poorly performing organizations. Propositions developed relate that process-oriented executives use both analytical measures and intuition in decision making, whereas outcome-oriented respondents rely more heavily on analytical measures. Practical implications: Service executives apparently make ethical decisions while focusing either on processes or on outcomes; members of these two groups use different evaluative criteria to identify a successful decision. Decisions relating to people within the organization are perceived by the executives to be especially salient, apparently owing to interpersonal interaction in services. Social implications: There are inherent social implications when ethical decisions are made, because these decisions determine which individuals or groups benefit, and which suffer. Originality/value: This research is among the first to interview high-level service executives about their ethical decision making when their choices define culture and values within their organizations. Findings offer a new look at how differences between executives that focus on processes and those that focus on outcomes may shape organizational cultures and lead to consideration of different criteria in making and evaluating decisions.